Combined therapy (intravitreal bevacizumab plus verteporfin photodynamic therapy) versus intravitreal bevacizumab monotherapy for choroidal neovascularization due to age-related macular degeneration: a 1-year follow-up study - Saviano, Sandro; Leon, Pia Easter; Mangogna, Alessandro; Tognetto, Daniele (Digital Journal of Ophthalmology, 2016)
Purpose To assess the efficacy and safety of combined intravitreal bevacizumab and low-fluency-rate photodynamic therapy (PDT) in the treatment of choroidal neovascularization (CNV) associated with age-related macular degeneration (AMD) and to compare it with intravitreal bevacizumab monotherapy. Methods A total of 62 eyes of 62 patients with angiographic evidence of CNV were divided into 2 groups: the eyes of one group were treated with a combined therapy of 1 intravitreal bevacizumab injection (1.25 mg) and PDT within 7 days; the eyes of the other group received intravitreal bevacizumab monotherapy. Clinical evidence of complications, best-corrected visual acuity (BVCA) and fluorescein leakage were evaluated. Best-corrected visual acuity and optical coherence tomography (OCT) were tested monthly and followed for 12 months. Results In the combined group the mean BCVA increased from 0.61 logMAR before the treatment to 0.54 logMAR at 12 months’ follow-up. In the monotherapy group the mean BCVA increased from 0.65 logMAR to 0.60 logMAR at 12 months’ follow-up. There was no significant difference in visual acuity outcomes between groups (P > 0.05). In the combined group the mean number of treatments was 1.19 per patient; in the monotherapy group, 5.31 per patient (P < 0.01). Conclusions Combined therapy appears to be an effective option for CNV associated with AMD treatment allowing a significant reduction of intravitreal injections.